Using sentiment analysis & machine learning for security price forecasting - Roy, Jyotirmoy; Nayeem, Abdullah Al Raihan (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.